GITA BAHANA NUSANTARA AS A REPRESENTATION OF BHINNEKA TUNGGAL IKA - Adira Hesti Ksvara (Universitas Negeri Makassar, 2022)
The purpose of this study is to describe Gita Bahana Nusantara as a musical group that represents diversity and strengthens the value of patriotism for the participants involved. This research uses the descriptive qualitative method. The results of the study found that Gita Bahana Nusantara has become a space for diversity that is applied by bringing together individuals from various regions in Indonesia so as to create brotherly ties as fellow Indonesians. In addition, patriotism also emerged in the participants involved through the media of music, namely struggle songs. The lyrics and the type of song can stir the hearts and souls of the people who sing and even those who listen to the song.